Effects of Emotions, Topic Beliefs, and Task Instructions on the Processing and Memory for a Dual-Position Text. Issue 1 (7th February 2022) - Bohn-Gettler, Catherine M.; McCrudden, Matthew T.
ABSTRACT: We examined whether positive emotions interacted with task instructions and topic beliefs to influence processing and memory of a dual-position text. Participants provided emotion and belief ratings, were instructed to focus on one position in a dual-position text while reading silently (Experiment 1) or thinking-aloud (Experiment 2), and then orally remembered the text. Independently of beliefs, higher positive emotion was associated with assimilative processes (backward inferences and elaborations). However, participants with higher positive emotion used more inferential processes for belief-consistent text, but spent more time reading and rehearsing belief-inconsistent text. Participants with lower positive emotion used more inferential processes for belief-inconsistent text, but spent more time reading and rehearsing belief-consistent text. Finally, participants in all groups provided supportive evaluations for belief-consistent text and refutational evaluations for belief-inconsistent text. The results are discussed in the context of theories of emotion and discourse comprehension.